Live Imaging of Immune Responses in Experimental Models of Multiple Sclerosis - Rossi, Barbara; Constantin, Gabriela (Frontiers in Immunology, 2016)
Experimental autoimmune encephalomyelitis (EAE) is the most common animal model of multiple sclerosis (MS), a chronic inflammatory autoimmune disease of the central nervous system (CNS) characterized by multifocal perivascular infiltrates that predominantly comprise lymphocytes and macrophages. During EAE, autoreactive T cells first become active in the secondary lymphoid organs upon contact with antigen presenting cells (APCs), and then gain access to CNS parenchyma, through a compromised blood–brain barrier, subsequently inducing inflammation and demyelination. Two-photon laser scanning microscopy (TPLSM) is an ideal tool for intravital imaging because of its low phototoxicity, deep tissue penetration and high resolution. In the last decade, TPLSM has been used to visualize the behavior of T cells and their contact with APCs in the lymph nodes and target tissues in several models of autoimmune diseases. The leptomeninges and cerebrospinal fluid represent particularly important points for T cell entry into the CNS and reactivation following contact with local APCs during the preclinical phase of EAE. In this review, we highlight recent findings concerning the pathogenesis of EAE and MS, emphasizing the use of TPLSM to characterize T cell activation in the lymph nodes and CNS, as well as the mechanisms of tolerance induction. Furthermore, we discuss how advanced imaging unveils disease mechanisms and helps to identify novel therapeutic strategies to treat CNS autoimmunity and inflammation.